(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
Spherical cameras are being used more frequently in surveying because of their low cost and possibility to process spherical images with conventional SfM methods. Fish-eye lenses are now frequently found on modern 360° cameras, allowing for the capture of the entire scene and subsequent model reconstitution by a non-photogrammetrist specialist. Gyrospherics are a feature of cameras that ensure image stabilization to reduce blur when the camera is moving. This feature allows it to capture moving scenes in time-lapse mode. However, two main factors - hardware parameters and software algorithms - affect the quality of the images that are captured. The 360° camera design allows for a variety of data processing methods by SfM. These images were created using multiple image sensors and lenses from each 360° camera. These images can be processed individually or by applying rules to define relationships between images. Also, images from cameras can be stitched and processed with a spherical camera model. In this paper is proposed processing methods of data from 360° cameras and estimated accuracy of each method.